The Effectiveness of Animiz Application Based Instructional Video Media on Students’ Learning Interest - Hasani, Muhammad Khairul; Kurniawati, Wiwien; Purmadi, Ary; Wibawa, Restu (UNDIKMA, 2026)
This study aimed to determine the effectiveness of Animiz application–based instructional video media in improving the learning interest of Grade VIII students in Indonesian language subjects at SMP IT Liddarain NW Tangar during the 2024/2025 academic year.This study employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. Data were collected primarily through questionnaires, supported by interviews and documentation. The data were analyzed using statistical techniques, including the Chi-Square test, N-Gain analysis, and SPSS.The Chi-Square analysis resulted in a calculated value of 14.305, while the critical Chi-Square value at 4 degrees of freedom and a 5% significance level was 9.488. Since the calculated value exceeded the critical value (14.305 > 9.488), the null hypothesis was rejected. Furthermore, the normalized gain (N-Gain) analysis showed an increase of 0.27, indicating a moderate improvement in students’ learning interest after the implementation of Animiz-based video learning media. SPSS analysis further confirmed that the use of Animiz-based instructional video media significantly increased students’ learning interest.In conclusion, this study demonstrates that Animiz application–based instructional video media are effective in enhancing students’ learning interest in Indonesian language subjects.